FOOD SECURITY AND POPULATION GROWTH IN NIGERIA - Hyacinth, IWU, Nnaoma (IJRDO - Journal of Social Science and Humanities Research, 2020)
There is growing knowledge that food security is hampered by population explosion in sub-Saharan Africa. This paper interrogates the interface between population growth rate and food security in Nigeria. Food insecurity does not only reflect on the number of times an individual can afford a meal in a day, it is also measured against the nutritional content. As population growth contributes annually about 4.5 million youths into the labour market, it raises the question of its implication on food security. Mechanized and export targeted agribusiness is adopted as contemporary policy measure to contain food insecurity. We ask, to what extent can mechanized and export oriented agribusiness address food insecurity in Nigeria. Two hundred and ten questionnaires respectively were administered to six farm settlements, three in Ekiti and Ondo South-West Nigeria known to be among the largest food producing states in Nigeria. The focus was on yam, cassava and fruits farmers using purposive sampling techniques. Access to land was not a major problem but other challenges like bad road, high cost of transportation, climate change and insufficient funds. Fear of imminent food insecurity was sustained necessitating advocacy on re-contextualization of the nexus between food security and population growth in Nigeria.